2007
DOI: 10.1016/j.jcp.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive particle management in a particle-in-cell code

Abstract: In particle-based plasma simulation, when dealing with source terms such as ionization, emission from boundaries, etc., the total number of particles can grow, at times, exponentially. Problems involving the spatial expansion of dynamic plasmas can result in statistical under representation of particle distributions in critical regions. Furthermore, when considering code optimization for massively parallel operation, it is useful to maintain a uniform number of particles per cell. Accordingly, we have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…We have found that when applied to the management of kinetic particles this algorithm can be somewhat more efficient in controlling the rapid growth of macro-particle numbers than the original particle coalescence model. 14 The kinetic remap closely follows the Lsp particle coalescence model, 14 in which a bilinear weighting scheme is used to combine the particle momenta and charge weights in a cell in order to create a momentum probability distribution function (pdf) for that cell. Replacement particles are generated from the distribution in a way that conserves charge, energy, and momentum globally and locally.…”
Section: Appendix: a Kinetic Particle Remap Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that when applied to the management of kinetic particles this algorithm can be somewhat more efficient in controlling the rapid growth of macro-particle numbers than the original particle coalescence model. 14 The kinetic remap closely follows the Lsp particle coalescence model, 14 in which a bilinear weighting scheme is used to combine the particle momenta and charge weights in a cell in order to create a momentum probability distribution function (pdf) for that cell. Replacement particles are generated from the distribution in a way that conserves charge, energy, and momentum globally and locally.…”
Section: Appendix: a Kinetic Particle Remap Algorithmmentioning
confidence: 99%
“…Critical to the application of this fully kinetic particle treatment is use of an algorithm that manages the total particle count by species while preserving the local momentum distribution functions and conserving charge. 14 Previous computational models of streamer/leader formation and dynamics have included electrostatic kinetic, 15,16 and fluid descriptions including adaptive mesh refinement techniques and moving meshes. [17][18][19] For example, detailed simulations in electronegative gases have been carried out in 2D (Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aspect ratios of the grid are allowed to be relatively large because the electromagnetic fields are solved implicitly. Approximately 12 and 36 particles per cell are adaptively maintained [15] for the Ar + and e − particles (both injected and ionized populations), respectively.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Hewett used computational particles with internal energy in which the error could be accumulated [2]. Assous and then Welch designed methods of merging values to grid nodes and redistributing the moments to particles [3,4]. Though exact energy and momentum conservation is possible with these methods, they are considerably more complicated than the original naive 2:1 merge.…”
mentioning
confidence: 99%